2008
DOI: 10.1073/pnas.0800293105
|View full text |Cite
|
Sign up to set email alerts
|

Txnip balances metabolic and growth signaling via PTEN disulfide reduction

Abstract: Thioredoxin-interacting protein (Txnip) inhibits thioredoxin NADPH-dependent reduction of protein disulfides. Total Txnip knockout (TKO) mice adapted inappropriately to prolonged fasting by shifting fuel dependence of skeletal muscle and heart from fat and ketone bodies to glucose. TKO mice exhibited increased Akt signaling, insulin sensitivity, and glycolysis in oxidative tissues (skeletal muscle and hearts) but not in lipogenic tissues (liver and adipose tissue). The selective activation of Akt in skeletal m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
225
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 197 publications
(238 citation statements)
references
References 40 publications
11
225
2
Order By: Relevance
“…Other groups have previously shown that TXNIP deficiency induces AKT activation via oxidative inactivation of PTEN in the soleus muscle and heart, and TXNIP is phosphorylated by AKT in response to insulin (Hui et al, 2008; Waldhart et al, 2017). To elucidate the correlation between TXNIP and AKT, we examined whether TXNIP interacts with AKT in cells.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Other groups have previously shown that TXNIP deficiency induces AKT activation via oxidative inactivation of PTEN in the soleus muscle and heart, and TXNIP is phosphorylated by AKT in response to insulin (Hui et al, 2008; Waldhart et al, 2017). To elucidate the correlation between TXNIP and AKT, we examined whether TXNIP interacts with AKT in cells.…”
Section: Resultsmentioning
confidence: 99%
“…To examine the effect of TXNIP or AKT on glucose uptake in vivo, we performed a glucose tolerance test (GTT) on fasted WT and KO mice (Hui et al, 2008). KO mice showed more significant glucose tolerance than WT mice from the beginning of the experiment, and glucose tolerance was significantly decreased by AKT inhibition in both WT and KO mice from 2 hr later (Figure 4a).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations